Science Comics and Educaplay Associated With Cognitive Gains in Science Learning: Komik Sains dan Educaplay Berkaitan dengan Peningkatan Hasil Belajar Kognitif - Rutialianisa Rutialianisa; Ellianawati Ellianawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Science learning frequently involves abstract concepts that are difficult for students to understand through text-based explanations alone, creating a need for multimodal instructional media that combine visual representation, narrative, and interactivity. Specific Background: Two accessible forms of multimodal media widely used in science education are science comics and the Educaplay quiz platform, both designed to support conceptual understanding and interactive engagement in classroom learning. Knowledge Gap: Despite increasing publications on multimodal learning tools, previous studies largely examine individual media within limited contexts and rarely provide a systematic overview of research trends and synthesized findings related specifically to science comics and Educaplay in science education. Aims: This study analyzes publication trends and synthesizes research findings on the use of science comics and Educaplay in relation to students’ cognitive learning outcomes in science learning during the 2021–2025 period. Results: Using a Systematic Literature Review following PRISMA 2020 guidelines, 22 eligible articles were selected from 385 identified studies. The synthesis shows consistent positive learning gains associated with both media, with an average effect size of 0.69. Science comics support visualization of abstract scientific concepts and promote emotional engagement through narrative representation, while Educaplay provides interactive quiz-based activities and immediate feedback that strengthen student participation and conceptual retention. Research trends reveal a transition from media validation studies toward classroom implementation and multimodal integration. Novelty: This review provides a consolidated analysis of research developments and learning outcomes related to science comics and Educaplay within science education literature from 2021–2025. Implications: The findings suggest that integrating narrative-based visualization and interactive quiz platforms may support multimodal science learning, while future studies are encouraged to explore longitudinal evaluation and adaptive media development. Highlights • Science comics facilitate visualization of abstract scientific concepts and narrative-based learning engagement.• Educaplay quizzes provide interactive activities with rapid feedback supporting conceptual retention.• Research progression shows a shift from media validation studies toward multimodal classroom integration. Keywords Multimodal Media; Science Comics; Educaplay Platform; Cognitive Learning Outcomes; Science Education